2012
DOI: 10.1073/pnas.1217668109
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen dependent activation function of ERβ is essential for the sexual behavior of mouse females

Abstract: We previously generated and characterized a genuine estrogen receptor (ER) β-null mouse line (named ERβ ST L−/L− ) and showed that ERβ ST L−/L− mice were sterile, due to an ovulation impairment in females and to an unknown reason in males, as their reproductive organs and spermatozoid motility appeared normal. We report here an assessment of the sexual behavior of ERβ ST L−/L− null mice. We found that ERβ ST L−/L− males display mildly impaired sexual behavior and that ERβ ST L−/L− females are significantly les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 99 publications
1
16
0
Order By: Relevance
“…Most of the actions of estrogens appear to be mediated by three receptors; that is, the estrogen receptors alpha (ERα), beta (ERβ), and G protein‐coupled receptor 30 (GPR30, Antal et al . ; Adlanmerini et al . ; Chimento et al .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the actions of estrogens appear to be mediated by three receptors; that is, the estrogen receptors alpha (ERα), beta (ERβ), and G protein‐coupled receptor 30 (GPR30, Antal et al . ; Adlanmerini et al . ; Chimento et al .…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the ERα subtype by its specific agonist propyl‐pyrazole triol (PPT) induces the expression of PRs and increases the number of PR‐immunoreactive neurons in the VMNvl , enhances proceptive behaviors, and increases lordosis quotients . None of these effects has been reproduced by activation of the ERβ subtype , which, in contrast to ERα activation, promotes high rejection quotients both in ER knockout mice and in rats injected with the ERβ‐specific agonist diaryl‐propionitrile (DPN) . There is also evidence that ERβ can modulate ERα activity in a dose‐dependent manner and regulate ERα‐mediated gene transcription .…”
Section: Introductionmentioning
confidence: 99%
“…ERβ is highly expressed in ovarian granulosa cells where it is required for effective ovulation (Couse et al 2005; Rodriguez et al 2010). Additional studies have suggested ERβ has a role in prostate cancer (Antal et al 2012; Hartman et al 2012). Together, these processes highlight the importance of regulated ERβ signaling.…”
Section: Introductionmentioning
confidence: 99%